Hubungan Ekspresi E-cadherin dengan Derajat Histopatologik dan Tumor Budding pada Karsinoma Endometrium Jenis Endometrioid - Pemuda, Haris; Asri, Aswiyanti; Zuryati Nizar, Rachmadijah; Yetti, Husna (Majalah Patologi Indonesia, 2022)
BackgroundEndometrial carcinoma is the fourth most common malignancy among women worldwide with increasing incidence and death rate every year. One of the types of endometrial carcinoma is endometrioid carcinoma, originated from atypical hyperplasia and develop into carcinoma. Lack of intercellular cohesiveness in the epithelial tumors such as endometrioid carcinoma occur due to lack of expression of E-cadherin. It can also causetumor invasion and metastatic through the epithelial-mesenchymal transition (EMT) process. Tumor differentiation and tumor budding are presumed to be histopathologic representations due to lack of cohesiveness and the occurrence of the EMT process so that these two things need to be related with the expression of E-cadherin on tumor cells.MethodsAn observational study was conducted using a cross-sectional approach with 46 cases of endometrioid endometrial carcinoma.Samples were obtained from 4 Anatomical Pathology Laboratories in West Sumatra during 2016-2019 in the form of paraffin blocks and HE slides that obtained from hysterectomy surgery. Reevaluation of tumor grade and tumor budding in HE slides was performed. E-cadherin expression in tumor cells was seen by immunohistochemical staining. Bivariate statistical analysis was performed using Fisher's Exact test and the results were considered significant if the p value was <0.05.ResultsSpecimens with negative E-cadherin expression were more common in grade 2 tumors (41.7%) and grade 3 tumors (50.0%) and in specimes with positive tumor budding (91.7%). Statistical analysis revealed a significant correlation between E-cadherin expression with tumor grade (p=0.000) and tumor budding (p=0.000).ConclusionExpression of E-cadherin has a significant correlation with the tumor grade and tumor budding in endometrioid endometrial carcinoma.